Functional superhydrophobic surfaces made of Janus micropillars. Issue 3 (21st November 2014) - Mammen, Lena; Bley, Karina; Papadopoulos, Periklis; Schellenberger, Frank; Encinas, Noemí; Butt, Hans-Jürgen; Weiss, Clemens K.; Vollmer, Doris
Abstract : Particle coated micropillar arrays having hydrophobic sidewalls and hydrophilic silica tops are fabricated, enabling the top sides to be selectively post-functionalized. The so termed Janus pillars remain in the Cassie state even after chemical modification of the top faces. Abstract : We demonstrate the fabrication of superhydrophobic surfaces consisting of micropillars with hydrophobic sidewalls and hydrophilic tops, referred to as Janus micropillars. Therefore we first coat a micropillar array with a mono- or bilayer of polymeric particles, and merge the particles together to shield the top faces while hydrophobizing the walls. After removing the polymer film, the top faces of the micropillar arrays can be selectively chemically functionalised with hydrophilic groups. The Janus arrays remain superhydrophobic even after functionalisation as verified by laser scanning confocal microscopy. The robustness of the superhydrophobic behaviour proves that the stability of the entrapped air cushion is determined by the forces acting at the rim of the micropillars. This insight should stimulate a new way of designing super liquid-repellent surfaces with tunable liquid adhesion. In particular, combining superhydrophobicity with the functionalisation of the top faces of the protrusions with hydrophilic groups may have exciting new applications, including high-density microarrays for high-throughput screening of bioactive molecules, cells, or enzymes or efficient water condensation. However, so far chemical attachment of hydrophilic molecules has been accompanied with complete wetting of the surface underneath. The fabrication of superhydrophobic surfaces where the top faces of the protrusions can be selectively chemically post-functionalised with hydrophilic molecules, while retaining their superhydrophobic properties, is both promising and challenging.